Comparative Analysis of Speech and Thought Presentation in Islamic Preach Between Zakir Naik and Syeikh Khalid Yasin - Eeng Zahara; Hermawati Syarif (English Language and Literature, 2019)
Through stylistics analysis, there are several stylistics devices which can be used by the linguists in order to develop that study whether in fiction or non-fiction text. In this paper, the theory of speech and thought presentation which is introduced by Leech and Short (1981) is used in analyzing the Islamic preach of two different speakers, Zakir Naik and Syeikh Khalid Yasin. Moreover, there are two research questions which come in this research (1) What are the modes of speech and thought presentation used in the Islamic preach of Zakir Naik and Syeikh Khalid Yasin and (2) what are the differences and similarities of speech and thought presentation modes used by this two different speakers? Therefore, the purpose of this reserach is to find out the modes of speech and thought presentation used by Zakir Naik and Khalid Yasin, and also to find out the similatities and differences between them. This is a comparative qualitative study because it is not in statistical data and it compares the modes of speech and thought presentation in eight video transcriptions to see the similarities and differences between two Islamic preachers. The results of the study show that (1) the modes of speech and thought presentation used by this two preachers is mostly similar in which the high number occurance is narrator’s presentation of voice and (2) it is found that Zakir Naik mostly used speech presentation rather than Khalid Yasin.